2010
DOI: 10.1245/s10434-010-1257-z
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life After Breast-Conserving Surgery and Intraoperative Radiotherapy for Breast Cancer Using Low-Kilovoltage X-rays

Abstract: Patients with early breast cancer after BCS and IORT with or without EBRT present with comparable QoL like patients receiving EBRT without a boost. IORT patients show the lowest rate of breast symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 52 publications
3
36
0
Order By: Relevance
“…Some of our data confirm a previous study by our group reporting on fewer breast symptoms and less general pain symptoms after IORT alone compared to IORT as a tumor bed boost followed by EBRT in breast cancer patients treated outside of the TARGIT-A trial [7]. In the present study, a single-center subgroup of patients of the TARGIT-A trial treated with IORT alone were found to have a significantly better radiation-related QoL than those treated with EBRT as assessed by restrictions in daily activities (role functioning), general pain, breast, and arm symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…Some of our data confirm a previous study by our group reporting on fewer breast symptoms and less general pain symptoms after IORT alone compared to IORT as a tumor bed boost followed by EBRT in breast cancer patients treated outside of the TARGIT-A trial [7]. In the present study, a single-center subgroup of patients of the TARGIT-A trial treated with IORT alone were found to have a significantly better radiation-related QoL than those treated with EBRT as assessed by restrictions in daily activities (role functioning), general pain, breast, and arm symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…8 In some studies, low-energy radiographs followed by WBI was associated with double the risk of breast fibrosis (to 37.5%), increased patient-reported pain, and decreased patient-reported quality of life compared with WBI alone. [30][31][32][33] In contrast, other studies have reported outcomes with IORT followed by WBI that appear acceptable and comparable to either WBI alone or WBI with a conventional EBRT boost. [33][34][35] As such, the task force felt the combination of IORT and WBI should be used only with caution and limited to women with higher risk features on final pathology.…”
Section: Adverse Effectsmentioning
confidence: 96%
“…After LEX-IORT as a boost, fibrosis rates are in range with standard treatments [20,21]. Further quality of life is significantly better in LEX-IORT patients in comparison to patients with whole breast radiotherapy [22,23]. Welzel et al showed especially less breast and arm symptoms in LEX-IORT patients during an analysis of the TARGIT A patients in a single center [22].…”
Section: Discussionmentioning
confidence: 99%